2016
DOI: 10.5194/nhess-16-1841-2016
|View full text |Cite
|
Sign up to set email alerts
|

Developments in large-scale coastal flood hazard mapping

Abstract: Abstract. Coastal flooding related to marine extreme events has severe socioeconomic impacts, and even though the latter are projected to increase under the changing climate, there is a clear deficit of information and predictive capacity related to coastal flood mapping. The present contribution reports on efforts towards a new methodology for mapping coastal flood hazard at European scale, combining (i) the contribution of waves to the total water level; (ii) improved inundation modeling; and (iii) an open, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
199
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 58 publications
(82 reference statements)
3
199
1
Order By: Relevance
“…Dynamic inundation simulations have been shown to be more reliable (Ramirez et al, 2016). However, Vousdoukas et al (2016) have shown that VI can be a good surrogate when computational efficiency is the priority, as also demonstrated by Breilh et al (2013). In flatter terrains, VI tends to be outperformed by hydraulic models, or other empirical approaches, such as the flood index method (Dottori et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic inundation simulations have been shown to be more reliable (Ramirez et al, 2016). However, Vousdoukas et al (2016) have shown that VI can be a good surrogate when computational efficiency is the priority, as also demonstrated by Breilh et al (2013). In flatter terrains, VI tends to be outperformed by hydraulic models, or other empirical approaches, such as the flood index method (Dottori et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Extreme waves transfer large amounts of energy to the coast, applying huge stress to coastal installations and protection structures [Oumeraci, 1994;Van der Meer et al, 2016], accelerating sediment transport processes and coastal erosion [Masselink and Puleo, 2006;Vousdoukas et al, 2012b;Archetti et al, 2016;Masselink et al, 2016;Monioudi, 2016;Postacchini et al, 2017], and driving dune breaching [Matias et al, 2008;Roelvink et al, 2009] and inundation [Bertin et al, 2012;Vousdoukas et al, 2016b]. By modulating interactions between oceans and the atmosphere waves play an important role in the climate system [Hemer et al, 2012] and are likely to be affected by global warming.…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate costs and benefits of adaptation to sealevel rise (Fankhauser, 1995;Jonkman et al, 2004;Dawson et al, 2009Dawson et al, , 2011Klijn et al, 2012;Boettle et al, 2013a;Eijgenraam et al, 2014;Jongmann et al, 2014;Kind, 2014;Kreibich et al, 2014;Boettle et al, 2016), various categories are required -in particular (i) the change of frequency and magnitude of coastal floods (Eijgenraam et al, 2014;Dawson and Hall, 2006;Vousdoukas et al, 2016), (ii) the expected (direct, monetary) damage without adaptation (Bouwer, 2013;Prahl et al, 2016), (iii) the residual (direct, monetary) damage with adaptation (Kreibich et al, Published by Copernicus Publications on behalf of the European Geosciences Union. 766 S. Lenk et al: Costs of sea dikes 2014), and (iv) the construction costs of the adaptation measure (Jonkman et al, 2013;Aerts et al, 2013).…”
Section: Introductionmentioning
confidence: 99%